The methodology of the noble Qur’an in reforming the individual and society in the light of the Exegesis of Al-Maraghi: The Community of Al-Azhar University in Egypt as a reference / Mahmoud Mohamed Fathy Gouda Gad - Mahmoud Mohamed , Fathy Gouda Gad (2023)
The period of Al-Maraghi witnessed changes and fluctuations because of which corruption spread and its manifestations multiplied. Sheikh Al-Maraghiattempted the interpretation of the Noble Qur’an to treat the pathological phenomena with the Qur’an’s means. Due to the similarity between the present to the past in the aspects of corruption and the dire need forreform, this study this topic:“The Holy Qur’an’s Approach for Reforming Individuals and Community in light of Al-Maraghee exegesis: The Community of the Honourable Al-Azhar University as a Model”. The study adopted the inductive methodology and the descriptive analytical methodology. The study also used the field methodologyby means of a questionnaire that was conducted on the selected sample from the studycommunity. This study aimed at knowing therelationship between Shaikh Al-Maraghi’s life and his exegesis ofthe Holy Qur’an, clarifying the Holy Qur’an’s approach in reforming the individual and societyin light of the interpretation of Al-Maraghi, and showing the impact of the Al-Maraghi’s exegesis on reforming the individual and society within Al-Azhar University. This study found a group of results. The first is that reform in Islam is a comprehensive process involving individuals and community in all their aspects including the religion andthe world, and its topic is the human soul, people, and society. The second is that some of the most important channels for individual, intellectual and behavioral corruption that Al-Maraghi was eager to deal with in his exegesis are arrogance, anger, the perversion of lust, and imitation. The third is that there is a correlation between the straightness of the individualand the reform of society.According to the Al-Maraghi Exegesis, the reform of society depends on developing positivity towards community reform, the treatment of moral corruption in community, the reform of the relationship among the individuals, and the reform of the family, which represents the unity of building societies.The applied study agreed with the theoretical part presented by the researcher regarding Al-Maraghi and hisexegesis and the relationship of the political, social and intellectual reality to the exegesis of Al-Maraghi, the importance of reform for the individual and community due to the large and widespread corruption, and the necessity to follow the approach of the Noble Qur’an in reforming the individual and community.According to the application that there are a number of challenges facing reform inside Al-Azhar University, including: the general failure to perceive the nature of Qur’anic reform in the light of Al-Maraghi’sexegesis, and the lack of awareness of the danger of intellectual influences on the reform process of the individual and community.Al-Maraghi’s Exegesis affected greatly in two aspects: intellectual process and Behavioral process on reform in the Al-Azhar University, which made it a source of the approaches of reform and its meansfor researchers. The researcher recommended that approaches of exegetists should be studied in the twentieth century to clarifythe relationship of exegeses to social reality.